Vacant Property and The City: Triggering Urban Potentials - Lucchini, Chiara (Sens public, 2024)
Urban commons represent a unique opportunity for public authorities to proactively tackle the dismantling, abandonment and obsolescence of the built heritage generated in cities by social and economic transition processes (affecting both private and public heritage). In a moment when resources and opportunities are lacking, and deep changes are taking place in the real estate market dynamics, strengthening a UC-oriented perspective could help public authorities blend their direction, coordination, intervention and direct territorial investment action as they strive to gain more accountability. As a start, such an approach could focus on publicly owned properties, calling for a change in their valorisation and mobilization strategies: the attention no longer turns to (often failing) economic tools, but mostly to define new local development pathways where social, generative and usage values come into play. It is hence necessary to establish new definitions, categories and descriptions for public property, focusing on its potential as a trigger for new urban regeneration processes and urban commons generation. Based on an exercise of mapping the city of Turin’s public properties, this contribution discusses how information on these assets is currently collected and systematized, exploring the limits and opportunities of assessing vacant properties at city scale through data analysis and mapping.